Accuracy of the Axillary Temperature Screening Compared to Core Rectal Temperature in Infants. (June 2022) - Alayed, Yazeed; Kilani, Mohammed A.; Hommadi, Abdullah; Alkhalifah, Mohammed; Alhaffar, Dalal; Bashir, Muhammad
Purpose . To compare the sensitivity of axillary and rectal temperature in infants who presents to the emergency department with a recent history of fever. Methods . A single-center cross-sectional comparative study of 201 patients who presents with a recent history of fever. Infants Up to 12 months of age were included. Demographic characteristics such as age and gender, weight, mean axillary and rectal temperatures were documented. Fever is defined as rectal temperature >38°C as opposed to >37.4 in the axillary method. Results . The mean age was 6.1 ± 3.5 months. The mean (SD) rectal-axillary temperature difference was 0.8°C ± 0.7°C which was statistically significant ( P < .001). The sensitivity, specificity, positive predictive and negative predictive values of the axillary method for fever >37.4 were 79.34% (95% CI [73-84.9]), 14.3% (95% CI [0.36-57.9]), 96.2% (95% CI [95-97.2]), and 2.4% (95% CI [0.4-13.5]), respectively. Conclusion . The rectal method remains highly important for accurate and prompt diagnosis in infants.